Determination of arecoline in areca nut based on field amplification in capillary electrophoresis coupled with electrochemiluminescence detection. (2nd February 2012) - Xiang, Qian; Gao, Ying; Han, Bingyan; Li, Jing; Xu, Yunhong; Yin, Jianyuan
ABSTRACT A sensitive capillary electrophoresis–electrochemiluminescence (CE–ECL) assay with an ionic liquid (IL) was developed for the determination of arecoline in areca nut. The IL, 1‐butyl‐3‐methylimidazolium tetrafluoroborate (BMImBF4), was an effective additive improved not only the separation selectivity but also the detection sensitivity of the analyte. BMImBF4 in the separation electrolyte made the resistance of the separation buffer much lower than that of the sample solution, which resulted in an enhanced field amplified electrokinetic injection CE. ECL intensity of arecoline is about two times higher than that of the analyte with phosphate–IL buffer system. Resolution between arecoline and other unknown compounds in real samples was improved. Under the optimized conditions (ECL detection at 1.2 V, 16 kV separation voltage, 20 mmol/L phosphate with 10 mmol/L BMImBF4 buffer at pH 7.50, 5 mmol/L Ru(bpy)32+ and 50 mmol/L phosphate buffer in the detection reservoir), a detection limit of 5 × 10–9 mol/L for arecoline was obtained. Relative standard deviations of the ECL intensity and the migration time were 4.51% and 0.72% for arecoline. This method was successfully applied to determination of the amount of arecoline in areca nut within 450 s. Copyright © 2012 John Wiley & Sons, Ltd.